One-step hydrothermal synthesis of bimetallic oxides (NiO@Mn3O4) supported on rGO: A highly efficient electrode material for supercapacitors. (20th August 2021) - He, Xiyan; Cheng, Yuanyuan; Qi, Hongbin; Zhang, Yuxi
Highlights: The bimetallic oxides (Mn3 O4 and NiO) is combined on rGO as a novel electrode material. NiO@Mn3 O4 /rGO was synthesized through a simple one-step hydrothermal method. NiO@Mn3 O4 /rGO has Csp of 533.97 F/g at 1 A/g current density which with excellent specific capacitor. After 2000 charge and discharge cycles, it still retains a capacitance retention of 75% at higher 10 A/g current density. Abstract: The continuous development of novel renewable energy makes the composition electrode become more and more diversified, and the composition has been relied on the multiple chemical elements. As energy storage materials, graphene and transition metal oxides have been researched at home and abroad due to their particular advantages. NiO, Mn3 O4, and reduced graphene oxide (rGO) were synthesized the NiO@Mn3 O4 /rGO through a simple hydrothermal method. The morphology and structure of NiO@Mn3 O4 /rGO is characterized by SEM, TEM, EDS, XRD and XPS. The electrochemical results (cyclic voltammetry curve, galvanostatic charge discharge and electrochemical impedance spectroscopy) confirm that NiO@Mn3 O4 /rGO exhibits excellent electrochemical performance. The specific capacitance of NiO@Mn3 O4 /rGO has a 533.97 F/g at 1 A/g. After 2000 charge and discharge cycles, it still retains a 75% capacitance at higher 10 A/g current density. Graphical abstract: NiO@Mn3 O4 /rGO electrode material has been successfully synthesized through a simply one-step hydrothermal method, and shows excellent electrochemical performance. Image, graphical abstract